If you can cut, you can collage : from paper scraps to works of art - Chastain, Hollie; Quarry Books (Gloucester, Mass.) (Beverly, MA : Quarry Books, 2018)
"Collage is a wonderful creative outlet, particularly for people who want to make art, but don't feel they have the skills, or confidence, for other endeavors. You can still explore and experiment with color, composition, and various themes and end up with exciting and often unexpected results. If you Can Cut, You Can Collage takes some of the mystery out of collage through easy illustrated pages that show readers the basic techniques of collecting and cutting imagery, composing and adhering compositions, and then provides a wealth of exercises that get readers going on their own creative projects. We'll get you started with simple, focused, projects like making a collage with only circles, where you'll learn important concepts like how to create a focal point, how to use repetition successfully, how to achieve contrast, balance, symmetry, and more. You'll be incorporating vintage ephemera, typography and lettering, and even urban and found materials in no time!"--
Keywords: Collage -- Technique